ERROR ANALYSIS OF STUDENTS IN GRADE VI OF BUMIREJO ELEMENTARY SCHOOL 1 IN COMPLETING FLOWCHART DEBIT STORY PROBLEMS - Isni Ramadhantri; Andhi Achmad; Arvrian Sukoco; Kartika Crysti Suryandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Mathematics is very important for human life. Mathematics has been taught since elementary school. Even so mathematics remains a subject that is difficult for students to understand. One sub-material that is considered difficult is the story of flow discharge. With this, researchers are interested in conducting research that aims to find out the types of students' errors and the factors that cause errors in grade VI students of SD Negeri 1 Bumirejo in solving the flow discharge story. This research is a qualitative descriptive study with data collection techniques using questionnaires, interviews and test questions. The subjects of this study were 8 students taken from 33 students in grade VI randomly / Random Sampling. The results of our study indicate that there are 5 types of errors in students, namely (1) reading errors about the problem (2) errors in understanding the problem (3) problem transformation errors (4) process skill errors (5) answers writing errors. Factors that cause student error are students who do not understand the problem, students are less careful and careful in working on the problem and students do not understand some of the meaning of words in the math problem. Therefore we decided to conduct a research entitled "Error Analysis of Students in Grade VI of Bumirejo Elementary School 1 in Completing Flowchart Debit Story Problems".